Small scale experiments and Fe model validation of structural response during hydrogen vented deflagrations. (2nd April 2019) - Pini, T.; Hanssen, A.Grønsund; Schiavetti, M.; Carcassi, M.
Abstract: University of Pisa (UNIPI) conducted a series of vented deflagration tests at B. Guerrini Laboratory. The tests were part of the experimental campaign performed by UNIPI for the European HySEA project (Hydrogen Safety for Energy Applications). Experiments included homogeneous hydrogen-air mixture contained in an about 1 m 3 enclosure, called SSE (Small Scale Enclosure). The mixture concentration was variable between 10% and 18% vol. During the deflagrations, structural response was investigated by measuring the displacement of a test plate. The collected data were used to validate the FE model developed by IMPETUS Afea. In this paper experimental facility, displacement measurement system and FE model are briefly described, then comparison between experimental data and simulation results is discussed. Highlights: Experimental tests of hydrogen-air homogeneous mixture vented deflagration. Experimental measurement of different test plates displacement. Data analysis and discussion of experimental data collected during tests. FE model set up and description. Comparison between experimental data and FE model results.